Case of solitary pulmonary capillary hemangioma: Pathological features based on frozen section analysis. (December 2013) - Isaka, Tetsuya; Yokose, Tomoyuki; Ito, Hiroyuki; Washimi, Kota; Imamura, Naoko; Watanabe, Masato; Imai, Kentaro; Nishii, Teppei; Yamada, Kouzo; Nakayama, Haruhiko; Masuda, Munetaka
<x xml:space="preserve">Abstract</x> Solitary pulmonary capillary hemangioma (SPCH) is a rare benign lung tumor that must be distinguished from small and early lung cancers. Here, we report a case of SPCH for which we performed frozen section diagnosis. The patient was a 55‐year‐old Japanese woman. Five years before the operation, mixed ground‐glass opacity was detected by computed tomography in the left posterior basal segment of the lower lobe (S10). Because the interior tumor density of the ground‐glass opacity increased slightly, video‐assisted thoracic surgery wedge resection was performed. Frozen section diagnosis revealed a benign tumor without proliferation of atypical epithelial cells. The tumor had narrow alveolar lumens, thickened alveolar septa and a clear boundary separating it from normal lung tissue. The proliferated lumens varied in size and were lined with single layers of flat cells. After the operation, immunohistochemical staining of a paraffin section revealed that the thickened alveolar septa resulted from the proliferation of capillary vessels, the flat cells of which were positive for CD31 and CD34 and negative for podoplanin; the tumor was diagnosed as SPCH. Here, we discuss the pathological features of SPCH on frozen sections with reference to this case and review previous related reports.